A novel mutation in CYP17A1 gene leads to congenital adrenal hyperplasia: A case report - Majid Nazari; Mohammad Yahya Vahidi Mehrjardi; Nosrat Neghab; Mahdi Aghabagheri; Nasrin Ghasemi (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background Congenital adrenal hyperplasia is a rare autosomal recessive disorder where the mutation in P450 family 17 subfamily A member 1 gene (CYP17A1) is involved in its etiology. The disorder represents itself with low blood levels of estrogens, androgens, and cortisol that generally couples with hypertension, Hypokalemia, sexual primary amenorrhea, infantilism and in affected individuals. Case In this study, the CYP17A1 gene in a 14-year-old female was examined. The karyotype of the patient was 46, XX, and the analysis of the CYP17A1 gene by Sanger sequencing revealed a novel homozygous deletion c.1052-1054CCT which led to isolated 17,20-lyase deficiency. Conclusion In conclusion, this study report an in-frame deletion which results in isolated 17, 20-lyase deficiency, and the mutation might be used for diagnosis in other patients with distinctive clinical symptoms